Elements for the process and corpus of Quechua contemporary narrative - Espino Relucé, Gonzalo (2018)
The conquest of the letter meant for the Quechua speakers experimentation and exploration of new forms of expression. This has happened to half of the twentieth century, when in Cusco and Huanta spread the first stories and poems written by Quechuas writers. We propose that these narratives have been consolidated at the end of the twentieth century and at the beginning of the century, as independent manifestations that attain the conformation of a corpus impressive as well as representative. This research aims to increase the visibility of narrative Quechua’s corpus therefore, we take as a reference temporary 19802015 and sets its studies in the Quechua production of Peru. These narratives are part of the country’s modernization from the XX century; essentially written manifestations not their oral forms, although inevitably we will link to them.